Insight on the influence of nano zinc oxide on the thermal, dynamic mechanical, and flow characteristics of Poly(lactic acid)– zinc oxide composites. Issue 6 (25th April 2019) - Shojaeiarani, Jamileh; Bajwa, Dilpreet; Jiang, Long; Liaw, Joshua; Hartman, Kerry
Abstract : Composites of Poly(lactic acid) (PLA) and spherical zinc oxide (ZnO) nanoparticles were prepared using melt processing followed by injection molding. The effect of nanosized ZnO on the molecular structure, thermal properties, dynamic mechanical properties, and flow characteristics of PLA composites were analyzed. Scanning electron microscopy images illustrated the formation of ZnO aggregates through PLA matrix. The molecular weight of PLA‐ZnO experienced a substantial decline by 55%, suggesting the presence of ZnO provoked degradation of PLA during composite preparation. Glass transition temperature of PLA‐ZnO decreased by 18% as compared with pure PLA, confirming the deleterious role of ZnO in PLA. The ZnO nanoparticles acted as a reactant and increased the thermal degradation rate. However, the incorporation of ZnO into PLA increased the crystallinity up to 20% and the storage modulus of composites in glassy state by 10%. The higher peak value of tan δ in composites suggested the more viscous behavior, which was further supported by lower number average molecular weight. The complex viscosity of composites exhibited a large Newtonian region over low shear rate, followed by shear thinning phenomenon. A significant decrease (96%) in complex viscosity was observed with the addition of ZnO into PLA. POLYM. ENG. SCI., 59:1242–1249 2019. © 2019 Society of Plastics Engineers